Comparative transcriptome and physiological analyses unveil differential responses of Panax ginseng adventitious roots to iron vs. zinc deficiency - Zhang, Siyu; Wang, Chenguang; Zhong, Yun; Jin, Zhuo; Li, Xiangguo; Wu, Songquan (Frontiers in Plant Science, 2026)
Trace elements iron (Fe) and zinc (Zn) are essential nutrients for plant growth and development, and their deficiency significantly inhibits the physiological metabolism and bioactive compound accumulation of medicinal plants. As a high-value medicinal plant, Panax ginseng C.A. Mey. is susceptible to mineral nutrient stress, affecting its quality and yield. However, current research on the genetic regulatory mechanisms of Fe and Zn is relatively scarce. This study conducted a fundamental investigation by comparing the morphology, physiological metabolism, and transcriptome of P. ginseng adventitious roots under Fe and Zn deficiencies. Results showed that Zn deficiency more strongly inhibited biomass accumulation than Fe deficiency. Zn deficiency significantly reduced total ginsenoside content, whereas Fe deficiency specifically decreased protopanaxadiol-type ginsenosides. Transcriptome analysis identified 2388 and 1055 differentially expressed genes under Fe and Zn deficiency, respectively. Both deficiencies led to widespread downregulation of key ginsenoside biosynthetic genes, though Fe deficiency upregulated protopanaxadiol synthase (PPDS) and protopanaxatriol type ginsenosides (PPTS) expression, consistent with ginsenoside profiles. Iron and zinc deficiencies elicited distinct hormone-response patterns, characterized by broad alterations in auxin-related genes: iron deficiency suppressed jasmonic acid signaling but activated abscisic acid, whereas zinc deficiency suppressed abscisic acid. Additionally, cytokinin homeostasis was disrupted under both deficiencies, whereas ethylene signaling was enhanced, particularly under Fe stress. Fe deficiency triggered a typical Strategy I response, whereas Zn deficiency altered ZIP transporter expression. These findings reveal the specific expression changes of genes related to ginsenoside biosynthesis, hormone metabolic pathways, and Fe/Zn transport and homeostasis regulation in ginseng under iron deficient and zinc deficient stress conditions, laying a foundation for further in-depth research into the molecular response mechanisms of ginseng adventitious roots to iron and zinc deficiency during their growth and development.